2013
DOI: 10.1002/asia.201300515
|View full text |Cite
|
Sign up to set email alerts
|

New Aminobenzopyranoxanthene‐Based Colorimetric Sensor for Copper(II) Ions with Dual‐Color Signal Detection System

Abstract: One molecule, three faces: A new aminobenzopyranoxanthene (ABPX)‐based colorimetric sensor allows determination of changes in Cu2+ concentration by spectrophotometry and the naked eye. This quantitative, colorful, and simple method takes advantage of the unique protolytic reaction of ABPX in response to Cu2+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…4,6 Furthermore, a formation of aggregates is occasionally accompanied by a vivid color change, which can be easily detected by the naked eye and is advantageous for a practical sensory material. 1,2,8 According to the exciton theory, two interacting molecules can form either a blue-shifted and non-fluorescent dimer or a red-shifted and fluorescent dimer. 9,10 The former is called a H-aggregate, whereas the latter is assigned as a J-aggregate, depending on the values of the angle (y) between the longitudinal axes of the monomer transition moments (54.71o y o 901 is a H-aggregate, whereas 01 o y o 54.71 is a J-aggregate).…”
mentioning
confidence: 99%
“…4,6 Furthermore, a formation of aggregates is occasionally accompanied by a vivid color change, which can be easily detected by the naked eye and is advantageous for a practical sensory material. 1,2,8 According to the exciton theory, two interacting molecules can form either a blue-shifted and non-fluorescent dimer or a red-shifted and fluorescent dimer. 9,10 The former is called a H-aggregate, whereas the latter is assigned as a J-aggregate, depending on the values of the angle (y) between the longitudinal axes of the monomer transition moments (54.71o y o 901 is a H-aggregate, whereas 01 o y o 54.71 is a J-aggregate).…”
mentioning
confidence: 99%
“…It also increases the acidic nature of the soil, the acidified lake soil containing higher concentration of free Al 3+ ions in the surroundings and surface water is deadly to growing plants and aquatic craniate animals . Copper, as a trace element which holds third rank in our biological system due to its excellent electrochemical behaviour, also functions as a co‐catalyst in many fundamental physiological reactions in living organisms . However, lavish of copper ions in human system is highly toxic and large intake of copper could cause, high blood pressure, lethargy, etc .…”
Section: Introductionmentioning
confidence: 99%
“…In this aspect, we focus on the aggregation behavior of a fluorophore, which often provides unexpected and interesting properties, such as an abrupt increase in fluorescence or spectral changes in color and fluorescence. [13][14][15][16][17] Very recently, we have reported that replacing a phenyl group with a 4-(9-anthryl)phenylene group in rhodamine dyes can lead to the formation of a slipped-stacked self-assembly of TMR and SiR (TMR-An and SiR-An, respectively) without the help of additional templates. 7 In the presence of halide ions, SiR-An can undergo a spontaneous transition of the assembly pattern from parallel-stacked (H-aggregates) to slipped-stacked assemblies (J-aggregates, Fig.…”
Section: Introductionmentioning
confidence: 99%